Induction of Autophagy by Baicalin Through the AMPK-mTOR Pathway Protects Human Skin Fibroblasts from Ultraviolet B Radiation-Induced Apoptosis - Zhang JA; Luan C; Huang D; Ju M; Chen K; Gu H (Drug Design, Development and Therapy, 2020)
Jia-An Zhang,* Chao Luan,* Dan Huang, Mei Ju, Kun Chen, Heng Gu Institute of Dermatology, Jiangsu Key Laboratory of Molecular Biology for Skin Diseases and STIs, Chinese Academy of Medical Science & Peking Union Medical College, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kun Chen; Heng GuInstitute of Dermatology, Jiangsu Key Laboratory of Molecular Biology for Skin Diseases and STIs, Chinese Academy of Medical Science & Peking Union Medical College, 12 JiangWangMiao Street, Nanjing, Jiangsu 210029, People’s Republic of ChinaTel/Fax +86 25 85478030Email kunchen181@aliyun.com; doctor_guheng@hotmail.comBackground: Baicalin, a natural product isolated from Scutellaria radix, has been reported to exert anti-oxidant and anti-apoptotic effects on skin, but the underlying mechanism remains poorly understood. This study aimed to investigate the possible mechanism of anti-UVB effect of baicalin in human skin fibroblasts.Methods: Cell proliferation was estimated by CCK-8 Kit. Apoptotic incidence was detected by flow cytometry with Annexin V-PE/PI apoptosis detection kit. Autophagy was determined by the evaluation of fluorescent LC3 puncta and Western blotting. Cell signalling was analysed by Western blotting.Results: Baicalin exerted cytoprotective effects in UVB-induced HSFs. Moreover, baicalin increased autophagy and suppressed UVB-induced apoptosis of HSFs. Pretreatment with 3-MA, an autophagy inhibitor, attenuated baicalin-induced HSFs autophagy and promoted apoptosis. Baicalin activated AMPK, which leads to suppression of basal mTOR activity in cultured HSFs. Administration of compound C, an AMPK inhibitor, abrogated AMPK phosphorylation and increased mTOR phosphorylation and apoptosis compared with baicalin alone.Conclusion: Taken together, these results indicate the important role of mTOR inhibition in UVB protection by baicalin and provide a new target and strategy for better prevention of UV-induced skin disorders.Keywords: autophagy, baicalin, ultraviolet B, apoptosis, AMPK